The Effect of Learning Styles on Students’ Creativity in Biology Classes at SMAN 5, Jambi City - Ramadhani, Rira; Johan Wicaksana, Ervan; Arisandy Eka Putra Sembiring, Dian (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2026)
Creativity is one of the key skills that needs to be developed in biology education because it encourages students to think innovatively and solve problems. However, the development of creativity is influenced by various factors, one of which is students’ learning styles. This study aims to analyze the influence of visual, auditory, and kinesthetic learning styles on student creativity at SMAN 5 in Jambi City. The study employed a correlational design with a quantitative approach, involving 168 11th-grade science students selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that visual learning styles (β = 0.272; p = 0.014 < sig. 0.05) and kinesthetic learning styles (β = 0.288; p = 0.003 < sig. 0.05) have a positive and significant effect on student creativity. This indicates that the higher the tendency toward visual and kinesthetic learning styles, the greater the students’ creativity, although their contributions are relatively small, with respective values of 0.045 (visual) and 0.053 (kinesthetic), while the auditory learning style does not have a significant effect (β = 0.297 > sig. 0.05). The coefficient of determination (R-square) value of 0.350 indicates that the three learning styles together account for 35% of the variance in student creativity, while the remainder is influenced by other factors outside the research model.